2022
DOI: 10.1039/d1fo03791a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral non-protein calorie supplements on nutritional status among maintenance hemodialysis patients with protein-energy wasting: a multi-center randomized controlled trial

Abstract: Protein-energy wasting (PEW) is prevalent in maintenance hemodialysis (MHD) patients, which is one of the major risk factors for poor outcomes and death. This study aimed to investigate the effects...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…On the basis of their intervention durations, the included studies were divided into a long-term intervention group (≥6 months) [ 23 , 29 , 30 , 34–36 , 40 , 43 , 44 ] and a short-term intervention group (<6 months) [ 24–26 , 31–33 , 37 , 38 , 41 , 42 ]. This subgroup analysis indicated that short-term ONS use increased serum albumin levels (2.32 g/l, 95% CI: 1.38–3.27, I 2 = 73.4%, P < 0.001) but long-term ONS use did not.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of their intervention durations, the included studies were divided into a long-term intervention group (≥6 months) [ 23 , 29 , 30 , 34–36 , 40 , 43 , 44 ] and a short-term intervention group (<6 months) [ 24–26 , 31–33 , 37 , 38 , 41 , 42 ]. This subgroup analysis indicated that short-term ONS use increased serum albumin levels (2.32 g/l, 95% CI: 1.38–3.27, I 2 = 73.4%, P < 0.001) but long-term ONS use did not.…”
Section: Resultsmentioning
confidence: 99%
“…Other subgroup analyses indicated that ONS improved serum albumin levels in patients on dialysis with malnourished [ 24 , 29 , 31 , 32 , 35 , 38 , 41 , 43 ] or unspecified malnourished status [ 23 , 25 , 26 , 30 , 33 , 34 , 36 , 37 , 40 , 42 , 44 ] and in those who were given protein/amino acid [ 23 , 25 , 26 , 29–31 , 33 , 35 , 37 , 40 , 44 ] or non-protein or mixed ONSs [ 24 , 32 , 34 , 36 , 38 , 41–43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the number of PEW studies has been increasing, and this phenomenon has been paid more and more attention by academic and clinical research (12,13). PEW's reasons involve a variety of aspects, such as insufficient nutritional intake, dialysis-related factors and other factors, which influence each other and synergistically increase the risk of patients with diseases (14). In addition, PEW can also cause problems such as hypocalcemia and hyperphosphatemia, which is also a cause of a range of symptoms in patients and is more common in MHD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, the tendency seemed to change. One important example is given by the completion of randomized studies assessing the efficacy of disparate interventions in dialysis patients: the role of cognitive therapies on depressive symptoms in HD patients, given the fact that depression belongs to the major outcomes of dialysis patients being directly related to the future risk for death [ 132 ]; the improvement in nutritional status in HD patients after administration of low protein calorie supplements [ 133 ]; the effect of exercise intervention on the 60-second sit-to stand test in HD patients, this latter on a topic with none evidence until 2020 [ 134 , 135 ]. Importantly, a recent randomized study enrolling more than 1300 patients undergoing HD, proved the significant reduction in mortality risk with hemodiafiltration compared to standard HD, confirming previous similar evidence specifically on CV mortality [ 129 ].…”
Section: Dialysis As Model Of Care and Researchmentioning
confidence: 99%